I- please ask a question. This is not a question
Answer:
3
Step-by-step explanation:
Answer:
(4t − 3) (t − 6)
Step-by-step explanation:
Using AC method:
Given a quadratic ax² + bx + c, find factors of ac that add up to b. Divide those factors by a and reduce. The denominators become the coefficients and the numerators become the constants.
Here, a = 4, b = -27, and c = 18.
ac = 4 × 18 = 72
Factors of 72 that add up to -27: -3 and -24
Divide factors by a: -3/4 and -24/4
Reduce: -3/4 and -6/1
So the factored expression is:
(4t − 3) (t − 6)
Answer:
If a number is even is the conditional statement.
Step-by-step explanation:
The phrase that starts with "if" is the hypothesis for conditional statement. The phrase that starts with "then" is conclusion for the statement.
Here, the statement is "If a number is even then it is divisible by 2".
Hypothesis = If a number is even
Conclusion = It is divisible by 2
Answer:
Step-by-step explanation:
<u>Given:</u>
- Loan amount = $700
- Interest rate = 7% simple
- Time = 3 years
<u>Interest amount:</u>